ELEMENTS OF CULTURE AND LOCAL WISDOM SA'O KEDA TRADITIONAL HOUSE (HOUSE OF CONSULTATIONS) WOLOTOPO VILLAGE, NDONA DISTRICT, ENDE DISTRICT: UNSUR BUDAYA DAN KEARIFAN LOKAL RUMAH ADAT SA’O KEDA (RUMAH MUSYAWARAH) DESA WOLOTOPO KECAMATAN NDONA, KABUPATEN ENDE - Anita (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
The problem in this research is, what is the process of making Sa'o Keda and what meaning is contained in making Sa'o Keda while the purpose of this research is to find out the process of making Sao Keda and the meaning of Sao Keda. The method used in this research is qualitative method. Qualitative research is a particular tradition within the social sciences that is fundamentally dependent on observing humans both in its field and in terms of it. The data collection techniques used were interviews, observation and documentation. The results showed that the process of making Sa'o Keda consisted of several stages including: Deliberation of traditional leaders (the Mosalaki), stages of searching for wood, cutting wood, stages of making Sao Keda. In the manufacturing stage of Sa'o Keda, there are several stages that are carried out, such as installing the Sa'o Keda poles, installing the Sa'o Keda supporting wood (Sarre Tenga), connecting the wood to the Sa'o Keda poles, and the last stage is making the roof from thatch leaves.